A, B, and C are polynomials, where A = n, B = 2n + 6, and C = n2 – 1. What is AB – C in simplest form?

–n2 + 3n + 5
n2 + 6n + 1
2n2 + 6n – 1
3n2 + 5

Respuesta :

Answer:

n^2 + 6n + 1

Step-by-step explanation:

Firstly, we have to evaluate AB

What we have to do is to multiply A and B

We have this as;

n(2n + 6) = 2n^2 + 6n

Now, we have to subtract the value of C from here and that is;

(2n^2 + 6n) - (n^2 - 1)

2n^2 + 6n - n^2 + 1

= 2n^2 -n^2 + 6n + 1

= n^2 + 6n + 1

Answer:

B

Step-by-step explanation:

ACCESS MORE